2017
DOI: 10.22616/erdev2017.16.n304
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of simmental cows Austrian selection

Abstract: Abstract. The article presents data characterizing milk production and milk quality indicators of Simmental cows' Austrian selection of different productive types in the process of adaptation for the conditions of foothills of the North Caucasus, the Russian Federation. Simmental cows' milk type by the amount of milk produced is surpassing the cows (meat-dairy and dairy-meat) at the first lactation on 815 and 1934 kg at the second lactation -904 and 2114 kg and at the third -834 and 2030 kg. Analysis of the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…Descriptive statistics (mean ± standard deviation) indicated that the average MY in this study increased gradually from parity 1 to 3 ( Table 2 ) and then decreased (parity 4: 6,660.04 ± 2,688.70 kg). The MY trend across parities was similar to that reported by different authors ( 34 , 35 ) for different European populations of Simmental cows. Milk composition plays an important role in countries like Italy where approximately the 75% of the total national milk annually produced is used for cheese manufacturing ( 36 – 38 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Descriptive statistics (mean ± standard deviation) indicated that the average MY in this study increased gradually from parity 1 to 3 ( Table 2 ) and then decreased (parity 4: 6,660.04 ± 2,688.70 kg). The MY trend across parities was similar to that reported by different authors ( 34 , 35 ) for different European populations of Simmental cows. Milk composition plays an important role in countries like Italy where approximately the 75% of the total national milk annually produced is used for cheese manufacturing ( 36 – 38 ).…”
Section: Resultssupporting
confidence: 89%
“…. similar to that reported by different authors (34,35) for different European populations of Simmental cows. Milk composition plays an important role in countries like Italy where approximately the 75% of the total national milk annually produced is used for cheese manufacturing (36)(37)(38).…”
Section: Overview Of the Studied Populationsupporting
confidence: 92%
“…Estas producciones de leche acumuladas fueron menores a lo reportado en literatura para ganado Simmental en países templados y tropicales (Pantelić et al 2009). Por ejemplo, Shevhuzhev et al (2017) reportaron en una población Simmental doble propósito en Austria producciones de 3123, 4245 y 5261 kg de leche a PL150, PL210 y PL305, respectivamente. Un valor más similar fue encontrado en una población de Rumania con una producción de leche a 305 días de 4053 ± 1392 kg (Nistor et al 2014).…”
Section: Resultados Y Discusiónunclassified
“…In this regard, in beef cattle breeding there is a tendency towards a transition from the extreme compact (solid) type with a short and square body on low legs to a type that is larger in live weight and well-defined meat forms [6][7][8].…”
Section: Introductionmentioning
confidence: 99%